Molecular Design, Synthesis and Docking Study of Alkyl and Benzyl Derivatives of Robustic Acid as Topoisomerase I Inhibitors. Issue 3 (14th February 2020) - Chen, Rui; Huang, Jiayong; Jaiswal, Yogini; Wei, Jianhua; Huo, Lini; Xia, Xing; Zhong, Jing; Williams, Leonard; Huang, Maochun; Liang, Yan
Abstract: Robustic acid is reported to be a bioactive compound, isolated from the medicinal plant Dalbergia benthamii Prain . Ten alkyl and benzyl derivatives (2a –2j ) of robustic acid were designed and synthesized based on molecular docking approaches. The biological activities of most of the synthesized compounds (such as 2g, 2h, and 2i ) were closely consistent with the docking results. In particular, 4‐ O ‐phenylpropyl substituted compound 2g displayed potent topoisomerase I inhibitory activity as well as cytotoxicity against SMMC‐7721, HepG2, and HeLa cell lines. Further biological testing suggests that compound 2g acted mainly by an arrest of the tumor cells in G1 phase of the cell cycle and suppressed cell proliferation by inducing apoptosis. The findings of this study are encouraging with respect to potential utilization of these compounds as new topoisomerase I inhibitors. Abstract :